Authority without territory : the Aga Khan development network and the Ismaili Imamate - Poor, Daryoush Mohammad; SpringerLink (Online service). (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Examining the connection between the concept of authority and the transformation of the Ismaili imamate, Authority without Territory is the first study of the imamate in contemporary times with a particular focus on Aga Khan, the 49th hereditary leader of Shi?a Imami Ismaili Muslims.
Keywords: Science; Science, general